Penggelapan Pajak Terhadap Pusat Pendidikan Pelatihan dan Sekolah Olahraga Nasional (P3SON) - I Gede Herry Budikusuma; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
Indonesia is a country consisting of sharing tribes, races, and cultures where each community has its own thoughts and understandings to live their lives. In carrying out his life, society is no stranger to the name of human rights where human behavior must not interfere with the rights of others and does not behave outside the norms that apply in accordance with positive laws. In carrying out a job ordinary people do it for the sake of earning income to support their families plus the needs of life that every day increase makes someone have to work hard to get income. But in the present day get income alone without getting dependents such as the absence of balance every worker must get income plus work safety dependents which later if one day happens something unwanted a worker can be dependents that will later be used for treatment and additional costs for himself and his family. The thing that happens when the situation of workers making a living is the occurrence of unwanted things where the project is stopped because the superiors commit tax evasion.